Additive manufacturing of mitral annuloplasty devices - Blake, Charlotte (2021)
Mitral valve annuloplasty is a common surgical procedure performed on thousands of patients each year across the world. A less invasive and more successful method of resolving mitral valve regurgitation, repair surgeries now outnumber replacement of the mitral valve in its entirety. As a result, a range of supportive annuloplasty ring devices for maintaining the surgical repair are now available for lifelong implantation. However, these devices underserve some populations leading to replacement surgeries, and rely on assumptions made on the natural, healthy anatomy of the mitral valve.